Serwisy streamingowe a lokalna branża audiowizualna – mapowanie wpływu Netflixa na polski sektor produkcji - Szostak, Sylwia (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
As a company, Netflix is currently demonstrating an unprecedented impact on audiovisual markets around the world. As a part of the global media dynamic, Poland is susceptible to changes resulting from the streaming platforms’ increasing intrusion into local audiovisual markets. While Anglo-American researchers have analyzed in depth the repercussions of Netflix’s involvement in local markets, in Poland the consequences of this media giant’s activities remain neglected in media studies. This article is an attempt to identify areas where Netflix’s impact on the Polish industry is significant and leads to visible changes in the industry’s existing practices and work system. As such, this article contributes to the emerging body of academic work, namely the platformization of the cultural sector, to which we can certainly assign audiovisual production. Based on in-depth interviews with industry practitioners and an analysis of the content produced for Netflix and its institutional positioning in Poland, the article maps the changes in the Polish audiovisual industry that are occurring here and now.